Aging and Income Convergence in Europe : A Survey of the Literature and Insights from a Demographic Projection Exercise - Crespo Cuaresma, Jesús; Loichinger, Elke; Vincelette, Gallina (Elsevier, 2016)
The current and projected low fertility levels for Europe and the continuous increases in life expectancy imply that the region will go through an unprecedented process of population aging, leading to sizable changes in the age structure of European societies. After reviewing the existing literature on the role played by demographic change as a determinant of economic growth and income convergence, with a focus on the European experience, we analyze the quantitative impact of the projected changes in the age and education composition of the labor force. Using newly available demographic projections, we show that the current demographic trends are expected to cause a slowdown in the speed of income convergence across European countries. Our projection exercise suggests that policies aimed exclusively at improving labor force participation do not appear to be sufficient to counteract the negative effects of aging on income convergence. Instead, we show that reducing the educational attainment gap between Central and Eastern European member states and the rest of the European Union in addition to increasing labor force participation leads to an accelerated pace of income convergence.